2016
DOI: 10.1509/jmr.13.0004
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Preferences for Annuity Attributes: Beyond Net Present Value

Abstract: Decisions about life annuities are an important part of consumer decumulation of retirement assets, yet are relatively underexplored by marketing researchers studying consumer financial decision-making. In this paper we propose and estimate a model of individual preferences for life annuity attributes using a choice-based stated-preference survey. Annuities are presented in terms of consumer-relevant attributes such as monthly income, yearly adjustments, period certain guarantees, and company financial strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 63 publications
6
43
0
Order By: Relevance
“…The importance of fairness as a predictor for liking of annuities was also documented in Shu et al (); this paper explores this finding, as well as other characteristics of individuals who dislike annuities, in much greater detail.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…The importance of fairness as a predictor for liking of annuities was also documented in Shu et al (); this paper explores this finding, as well as other characteristics of individuals who dislike annuities, in much greater detail.…”
supporting
confidence: 62%
“…Most recently, Brown, Kapteyn, Luttmer, and Mitchell (2017) find experimental evidence for narrow bracketing, demonstrating that survey respondents encouraged to think about spending during retirement are more likely to properly value annuities. In our prior work, we have found that information displays that help individuals "do the math" on the cumulative value of annuity payouts can affect both overall interest in annuities and demand for particular annuity attributes (Shu, Zeithammer, & Payne, 2016; see also Kunreuther, Pauly, & McMorrow, 2013). These behavioral explanations of the annuity puzzle provide important insights, but many more aspects of the decision remain to be investigated and tested.…”
Section: Research On Annuity Choicementioning
confidence: 99%
“…In both scenarios older participants tend to choose the lump sum whereas younger participants prefer the annuity. Therefore, the main hypotheses 1(a) and 1(b) are confirmed, see also Brown et al (2012) and Shu et al (2013) who find negative age effects using Croatian pension and survey data. In both scenarios all other demographic variables are insignificant.…”
Section: H1a and H1b: Annuitization By Age -Full Samplementioning
confidence: 54%
“…This result is supported by Chalmers and Reuter (2012) who find a positive connection between recent stock returns and the selection of the lump sum. Shu et al (2013) model and measure individual preferences for annuities using a conjoint survey. This technique allows them to separately elicit preferences for different attributes of the annuity (e.g., period certain, inflation adjustment).…”
Section: Behavioral Aspectsmentioning
confidence: 99%
“…The government could, for instance, emphasize the value of an annuity in ensuring that individuals do not outlive their financial resources while de-emphasizing how long an individual would need to live to get a positive return. 45,[74][75][76][77] Saving for Short-Term Needs Individuals have many reasons to save other than for retirement. They face known expenses for which they can plan, like the down payment for a house or college tuition for their children.…”
Section: Biased Judgments and Preferencesmentioning
confidence: 99%